TECHNICAL DIAGNOSTIC OF EQUIPMENT OF METALLURGICAL SHOPS, PERSPECTIVES OF DEVELOP-MENT - A. N. Kattsyn (Литьë и металлургия)
The technical diagnostics of the equipment of metallurgical shops, prospects of their development at RUP «BMZ» are considered.